A compact graphene based nano-antenna for communication in nano-network - M. Saravanan; V.R. Prakash (Institute of Advanced Engineering and Science, 2020)
Due to recent advances in nanotechnology, the use of nano-devices and its network becomes more popular in the field of medical, commercial and military applications. One of the major issues in designing nano-network is miniaturization of nano-devices which are limited due to communication antenna used in that device and its power constraints. At 1000nm size, an antenna resonates at around 100 THz which suffers from greater propagation loss and provides signal coverage of micrometer distances. Hence there is a need for nano-antenna with reduced size and also operating at mid infrared frequencies to provide a good signal coverage. In this paper, graphene-based nano-antenna is presented. The model resonates at 55THz frequency with a peak gain of 5.47 dB in the propagation direction. The model exploits the principle of surface plasma polarition waves for miniaturization and achieves 50% size reduction when compared to conventional nano-antenna and best suitable for nano-network communications.